Combined search for the Standard Model Higgs boson using up to 4.9 fb(-1) of pp collision data at root s=7 TeV with the ATLAS detector at the LHC - Onofre, A. (2012)
A combined search for the Standard Model Higgs boson with the ATLAS experiment at the LHC using datasets corresponding to integrated luminosities from 1.04 fb−1 to 4.9 fb−1 of pp collisions collected at View the MathML sources=7 TeV is presented. The Higgs boson mass ranges 112.9–115.5 GeV, 131–238 GeV and 251–466 GeV are excluded at the 95% confidence level (CL), while the range 124–519 GeV is expected to be excluded in the absence of a signal. An excess of events is observed around mH∼126 GeVmH∼126 GeV with a local significance of 3.5 standard deviations (σ ). The local significances of H→γγH→γγ, View the MathML sourceH→ZZ(⁎)→ℓ+ℓ−ℓ′+ℓ′− and View the MathML sourceH→WW(⁎)→ℓ+νℓ′−ν¯, the three most sensitive channels in this mass range, are 2.8σ, 2.1σ and 1.4σ , respectively. The global probability for the background to produce such a fluctuation anywhere in the explored Higgs boson mass range 110–600 GeV is estimated to be ∼1.4%∼1.4% or, equivalently, 2.2σ.